How does the country's economic performance affect the EU structural and cohesion fund absorption rate? - Petkova, Polina Plamenova (KDI School, 2012)
The purpose of this study was to investigate if GDP per capita of each EU member state has a determinative influence on the country’s ability to use financial resources from the EU Structural funds. In order to scientifically analyze this relationship I used descriptive methods for literature and empirical data study combined with a quantitative analysis in form of a fixed effects model. As a result of the study several observations occurred. First the EU fund absorption rate is significantly influenced by its economic performance and hence by its financial capacity. Second the absorption capacity has inherent complications and inherent problems e.g. measurement, monitoring and time discrepancies between countries. Based on the findings I recommend an extension of the conducted study which will involve statistics from current and future periods as well as additional key factors such as transparency, corruption. Thereupon a redefinition and precise execution and implementation of the EU financial instruments will be possible, which will increase funding efficiency and efficacy.
Thesis(Master) --KDI School:Master of Public Policy,2012